2014
DOI: 10.1186/s12879-014-0544-x
|View full text |Cite
|
Sign up to set email alerts
|

Social, economic, and health impact of the respiratory syncytial virus: a systematic search

Abstract: BackgroundBronchiolitis caused by the respiratory syncytial virus (RSV) and its related complications are common in infants born prematurely, with severe congenital heart disease, or bronchopulmonary dysplasia, as well as in immunosuppressed infants. There is a rich literature on the different aspects of RSV infection with a focus, for the most part, on specific risk populations. However, there is a need for a systematic global analysis of the impact of RSV infection in terms of use of resources and health imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 102 publications
(255 reference statements)
2
76
0
2
Order By: Relevance
“…What about the cost-effectiveness of administering prophylaxis for high-risk children? A UK study reported that the following high-risk groups fell within the economically viable £30 000/quality-adjusted life year: infants <24 months with CLD, CHD, preterm <32 weeks and preterm 33–35 weeks with risk factors15; this was supported by the conclusions of a systematic review which stated that palivizumab was cost-effective in improving outcomes in high-risk children 16. As the evidence suggests any child with DS is at risk of similar or even more severe RSV disease than others, the argument can also be made for including them from an economic perspective.…”
Section: Commentsmentioning
confidence: 93%
“…What about the cost-effectiveness of administering prophylaxis for high-risk children? A UK study reported that the following high-risk groups fell within the economically viable £30 000/quality-adjusted life year: infants <24 months with CLD, CHD, preterm <32 weeks and preterm 33–35 weeks with risk factors15; this was supported by the conclusions of a systematic review which stated that palivizumab was cost-effective in improving outcomes in high-risk children 16. As the evidence suggests any child with DS is at risk of similar or even more severe RSV disease than others, the argument can also be made for including them from an economic perspective.…”
Section: Commentsmentioning
confidence: 93%
“…10 La infección por virus sincicial respiratorio es una de las más comunes en la infancia y tiene considerable impacto sanitario, económico y social en el mundo entero. 11 A pesar de que, -en escenarios con adecuado acceso a la salud-, la enfermedad por VSR puede ser convenientemente manejada, la magnitud de esta patología implica un enorme consumo de recursos, lo que hace imprescindible una correcta planificación de las estrategias para enfrentarla. 12 Una mejor comprensión de los factores determinantes de la circulación del virus podrá contribuir a mejorar la eficiencia en el uso de recursos.…”
Section: Discussionunclassified
“…It is known that the socio-economic and cultural levels of families are risk factors in the development of bronchiolitis (25,26). The mother's level of education is important in infant nutrition.…”
Section: Discussionmentioning
confidence: 99%